(untitled) (The Pakistan Development Review, 2006)
This paper attempts to investigate the linkage between the excess money supply growth and inflation in Pakistan and to test the validity of the monetarist stance that inflation is a monetary phenomenon. The results from the correlation analysis indicate that there is a positive association between money growth and inflation. The money supply growth at first-round affects real GDP growth and at the second round it affects inflation in Pakistan. The important finding from the analysis is that the excess money supply growth has been an important contributor to the rise in inflation in Pakistan during the study period, thus supporting the monetarist proposition that inflation in Pakistan is a monetary phenomenon. This may be due to the loose monetary policy adopted by the State Bank of Pakistan to show the high priority of the growth objective. The important policy implication is that inflation in Pakistan can be cured by a sufficiently tight monetary policy. The formulation of monetary policy must consider development in the real and financial sector and treat these sectors as constraints on the policy. JEL classification: E31, C22, C32 Keywords: Money Supply, Inflation, Growth, Quantity Theory, Monetary Policy, Pakistan